2018
DOI: 10.1186/s40510-018-0204-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of orthodontic appliance-derived artifacts on 3-T MRI movies

Abstract: BackgroundMagnetic resonance imaging (MRI) has been used to study configurations of speech organs in the resting state. However, MRI is sensitive to metals, and numerous types of metallic appliances, most of which have a large magnetic susceptibility, are used in orthodontic treatment and may cause severe artifacts on MRI. We have developed techniques for obtaining MRI movies of the oral region, to evaluate articulatory changes, especially movement of the tongue, palate, and teeth, pre- and post-orthodontic/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…A classification of dental materials according to their magnetic susceptibility has been proposed [33], and studies have evaluated the effects of orthodontic fixed metal appliances [34] and retainers [35] on image quality. There is fair evidence to suggest that orthodontic devices cause MRI image artefacts both at 1.5 T [8] and 3 T [36]. The removal of metal orthodontic devices prior to MRI is thus recommended, especially if the area of interest is near the appliance [5,37], as in cervical vertebrae, cervical region, paranasal sinuses, and head and neck MRI scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A classification of dental materials according to their magnetic susceptibility has been proposed [33], and studies have evaluated the effects of orthodontic fixed metal appliances [34] and retainers [35] on image quality. There is fair evidence to suggest that orthodontic devices cause MRI image artefacts both at 1.5 T [8] and 3 T [36]. The removal of metal orthodontic devices prior to MRI is thus recommended, especially if the area of interest is near the appliance [5,37], as in cervical vertebrae, cervical region, paranasal sinuses, and head and neck MRI scans.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of metal orthodontic devices prior to MRI is thus recommended, especially if the area of interest is near the appliance [5,37], as in cervical vertebrae, cervical region, paranasal sinuses, and head and neck MRI scans. A brain and temporomandibular joint region MRI should not, however, require the removal of such appliances [36].…”
Section: Discussionmentioning
confidence: 99%
“…Because this posture might have affected the exact time course of deglutition, further studies to capture images in a sitting position should be conducted [ 22 ]. Finally, the dynamic images often become invisible or distorted and linear measurements may be incorrect because metallic appliances in the oral cavity, such as orthodontic appliances, produce a range of artifacts depending on the location and type of metal [ 23 ]. The authors concluded, however, that orthodontists should not necessarily remove all metallic appliances before MRI examination and that caution should be exercised when the distorted image is measured.…”
Section: Discussionmentioning
confidence: 99%
“…MR movies are suitable for the evaluation of tongue movement. According to a study of patients with orthodontic appliances, [29] it is difficult to analyze the state during orthodontic treatment using MR movies. However, to perform an MR movie before, during, and after MFT will be meaningful to improve patient motivation.…”
Section: Application Of Findings In the Treatment Of Tongue Thrustmentioning
confidence: 99%